Boletim Official do Governo da Provincia de Macau (IMPRENSA NACIONAL, 1902)
Stamp of St. Joseph Seminary
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Leao XIII, No Fausto Anniversario da sua Coroacao (O Collegio de S. Fiel, 1902)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Preces Matutinae et Vespertinae (In Missione Catholica, 1902)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Ve de la Mere Marie-Hermine de Jesus (Vanves Pres Paris, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Dictionnaire Francais- Cantonnais - Aubazac, Louis (Imprimerie de La Societe des Missions Etrangeres, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Conferencias Ecclesiasticas - Barroso, D. Antonio (Antonio Dourado, 1902)
Keywords: 1.Conservation 保護; 18.Bookworm; 18.Bookworm (Only Cover); 2.Damage

Theologia Pastorialis - Berardi, Aemilio (Novelli & Castellani, 1902)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Good

Manuale di Storia Ecclesiastica per uso di lezioni scolastiche e di studio privato - Castelletti, Carlo (Stab. Tip. S. Alessandro, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Petit Directoire du Pretre-Educateur au sortir du Seminaire - Dementhon, L'Abbe Charles (Gabriel Beauchesne, 1902)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Rubricarum breviarii, missalis et ritualis romani explanatio triplex - Dieusoitbéni, Joannes Josephus (Typis Societatis Missionum ad Exteros, 1902)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church China Hong Kong Liturgy Texts; China Hong Kong; Condition: Fair; Hard Cover; Liturgics; Religion; Texts; Église catholique Liturgie Textes

Elogio historico do Dr. José Augusto Nugueira S. Paio, reitor e professor do Lyceu Nacional d'Angra do Heroismo - Ferreira-Deusdado, Manuel Antonio (Brazilian and Portuguese history and culture: The Oliveira Lima Library, 1902)
Keywords: Sampaio, José Augusto Nogueira, 1827-1900

Institutiones Philosophiae Moralis - Ferretti, Augusto (Ex Officina Libraria Giachetti filii et Soc, 1902)
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover); 2.Damage; 8.Tear

Institutiones Philosophiae Moralis - Ferretti, Augusto (Ex Officina Libraria Giachetti filii et Soc, 1902)
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover); 2.Damage

Biblia Sagrada - Figueiredo, Antonio Pereira de (1902)
Keywords: 1.Conservation 保護; 2.Damage

Biblia Sagrada - Figueiredo, Antonio Pereira de (1902)
Keywords: 1.Conservation 保護; 2.Damage

Biblia Sagrada - Figueiredo, Antonio Pereira de (1902)
Keywords: 1.Conservation 保護; 2.Damage

Tractatus de Verbo Incarnato - Franzelin, Ioannis Bapt. (Ex Typographia Polyglotta, 1902)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

La Stele Chretienne de Si-Ngan-Fou - Havret, P. Henri (Imprimerie De la Mission Catholique, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Medulla Theologiae Dogmaticae - Hurter, H. (Libraria Academica Wagneriana, 1902)
Keywords: 1.Conservation 保護; Good

Medulla Theologiae Dogmaticae - Hurter, H. (Libraria Academica Wagneriana, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 6.Yellowing 變黃

Medulla Theologiae Dogmaticae - Hurter, H. (Libraria Academica Wagneriana, 1902)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Summa Theologica - Janssens, Laurentio (1902)
Keywords: 1.Conservation 保護; 2.Damage

rubricarum breviarii, missalis et ritualis romani - Joanne-Josepho Dieusoitbeni (Typis Societatis Missionum Ad Exteros, 1902)
Stemp of seminario diocesano de macau
Keywords: Good

Commentarius in Ecclesiasticum - Knabenbauer, Iosepho (Sumptibus P. Lethielleux, Editoris, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Theologia Moralis - Lehmkuhl, Augustino (Sumptibus Herder, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Theologia Moralis - Lehmkuhl, Augustino (Sumptibus Herder, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

La Vierge de Sora Sainte Restitute - Manoir, Jean du (Danves pres Paris, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Prediche Quaresimali - Maurizio, S. Leonardo d Porto (Tip. Emiliana Di G. B. Monauni, 1902)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Compendio de Theologia Gogmatica Especial Segundo a Mente de S. Thomaz D'Aquino - Miguel Ferreira d'Ollmeida (Typographia da Revista Catholica, 1902)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Oeures Completes de Saint Francois de Sales - Sales, S. Francisco de (Libraire de Louis Vives, Editeur., 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Sacra Liturgia - Stappen, J. F. Van der (Summi Pontificis, 1902)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Sacra Liturgia - Stappen, J. F. Van der (Summi Pontificis, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Compendio de Theologia Dogmatica - Tanquerey, S. S. (Typ. da Revista Cathokica, 1902)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage